Dynamic changes in aroma of large-leaf yellow tea during the whole processing at an industrial scale: From fresh leaf to finished tea - Jing Wang; Yuemeng Hu; Zhenyu Guan; Ronggang Zhai; Jieyao Yu; Marina Rigling; Yanyan Zhang; Xiaochun Wan; Xiaoting Zhai (Food Chemistry: X)
Large-leaf yellow tea (LYT) is a yellow tea product with a specific aroma characteristic and the flavor code has recently been revealed. To elucidate the transformation of odorants from fresh leaves to finished LYT, this study tracked dynamic changes in aroma compounds throughout an industrial-scale experiment. The odorants' contributions of each step were evaluated by stable isotope dilution assays, internal standard method, and odor activity values. Among 39 quantitated odorants, the loss of top-note compounds such as dimethyl sulfide, 2-/3-methylbutanal, and 2-methylpropanal during yellowing was compensated during roasting. In contrast, floral compounds like geraniol and linalool declined progressively, while pyrazines were mainly generated during the final roasting and increased with roasting intensity. Therefore, yellowing and roasting steps were identified as key processes influencing LYT aroma formation, and the roasting degree significantly influenced the final aroma profile. These findings provide a mechanistic understanding of aroma development in LYT and offer practical guidance for optimizing processing parameters to tailor flavor profiles.